2004
DOI: 10.1080/02701367.2004.10609134
|View full text |Cite
|
Sign up to set email alerts
|

Expert Golf Instructors' Student-Teacher Interaction Patterns

Abstract: The purpose of this study was to identify the dominant instructional interaction patterns of expert golf instructors. Instructors (N = 22) were selected by the Ladies Professional Golf Association (LPGA) Teaching based on the following criteria: (a) 10 or more years of golf teaching experience, (b) LPGA certification, (c) awards received for the quality of their instruction, and (d) peer and student recognition for outstanding teaching. The instructors were videotaped teaching a 60-min lesson to a novice colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…In terms of its contribution to the knowledge base on teaching and learning, this study adds to existing research on expert golf instruction (Baker et al 1998;Schempp et al 2004;Webster, Connolly, and Schempp 2009). This study also lends a novel perspective to the already well-established idea that expert teachers are more opportunistic and flexible in Physical Education and Sport Pedagogy their teaching than novice teachers (Berliner 2004).…”
Section: Discussionmentioning
confidence: 86%
“…In terms of its contribution to the knowledge base on teaching and learning, this study adds to existing research on expert golf instruction (Baker et al 1998;Schempp et al 2004;Webster, Connolly, and Schempp 2009). This study also lends a novel perspective to the already well-established idea that expert teachers are more opportunistic and flexible in Physical Education and Sport Pedagogy their teaching than novice teachers (Berliner 2004).…”
Section: Discussionmentioning
confidence: 86%
“…Instructors in the High rank group elicited less predictable student verbal and non-verbal responses and stimulated more student analytical nonverbal response than instructors in the Low or Mid rank groups. This suggests that the classes of High rank instructors had better communication, encouraging students to participate in creative ways, which is similar to expert golf instructors [Schempp 2004]. Coaches of more satisfied basketball teams similarly created environments where creative student responses were more likely than with coaches of less satisfied teams [Fisher 1982].…”
Section: Discussionmentioning
confidence: 93%
“…Byra and Sherman (1993) examined preactive and interactive decision making of more and less experienced preservice teachers, while Housner and Griffey (1985) and Griffey and Housner (1991) contrasted inexperienced and experienced teachers. In a recent study, Schempp, et al (2004) analyzed the student-teacher interaction patterns of expert golf instructors. These studies demonstrated that more experienced teachers develop sophisticated knowledge structures that enable them to manage students effectively, focus on student learning, and make adaptations during lessons to meet student needs.…”
Section: Teachers' Thought Processesmentioning
confidence: 99%